1992
DOI: 10.3109/00016489209137487
|View full text |Cite
|
Sign up to set email alerts
|

Retention Fluids of Chronic Sinusitis Induce Neutrophil Adherence to Microvascular Endothelial Cells

Abstract: The adherence of circulating leukocytes to the vascular endothelium is a critical step in the emigration of leukocytes through blood vessel walls to inflammatory lesions. The influence of nasal secretions on the adherence of neutrophils to the vascular endothelium was investigated using monolayers of human mucosal microvascular endothelial cells derived from the inferior turbinate. Preincubation of vascular endothelial cells with retention fluids from the maxillary sinus of the patients with chronic sinusitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…ICAM‐1, which is produced from vascular endothelial cells, epithelial cells, and fibroblasts in response to stimulation with proinflammatory cytokines, plays an important role in the accumulation of neutrophils. Previously, we demonstrated that IL‐1β mRNA is expressed in paranasal sinus mucosa and that a large amount of IL‐1β is contained in paranasal secretions of patients with chronic sinusitis 14,15 . Immunohistochemical staining revealed significant production of ICAM‐1 in endothelial cells of paranasal sinus mucosa 14 .…”
Section: Introductionmentioning
confidence: 84%
“…ICAM‐1, which is produced from vascular endothelial cells, epithelial cells, and fibroblasts in response to stimulation with proinflammatory cytokines, plays an important role in the accumulation of neutrophils. Previously, we demonstrated that IL‐1β mRNA is expressed in paranasal sinus mucosa and that a large amount of IL‐1β is contained in paranasal secretions of patients with chronic sinusitis 14,15 . Immunohistochemical staining revealed significant production of ICAM‐1 in endothelial cells of paranasal sinus mucosa 14 .…”
Section: Introductionmentioning
confidence: 84%
“…Tokushiga et al [14]proposed that IL–1β induces the expression of both intercellular adhesion molecule–1 (ICAM–1) and E–selectin on ECs, presumably leading to neutrophil infiltration. The increased adhesion of neutrophils to cultured human nasal microvascular endothelial cells (HNMECs) induced by sinus effusion was significantly inhibited by anti–IL–1β antibody [3]. In the same series of experiments, IL–1β induced the adherence of neutrophils to cultured HNMEC.…”
Section: Introductionmentioning
confidence: 93%
“…The recruitment and migration of inflammatory cells at sites of mucosal inflammation involve a variety of adhesion molecules [1]. Nonallergic chronic sinusitis is characterized by purulent paranasal sinus effusion and persistent nasal discharge with numerous emigrated neutrophils [2, 3, 4, 5, 6, 7, 8, 9], in additon to the accumulation of eosinophils in the tissue [5, 10, 11, 12, 13]. Tokushiga et al [14]proposed that IL–1β induces the expression of both intercellular adhesion molecule–1 (ICAM–1) and E–selectin on ECs, presumably leading to neutrophil infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…the specific expression of ICAM‐1 in both endothelium and epithelium. A recent study on the nasal smears in subjects with nonallergic chronic sinusitis showed that the main cellular component in the sinus effusion is an increased number of neutrophils, 10,12,13 whereas mucosal biopsies have been characterized by the number of lymphocytes, macrophages, and eosinophils 1 . It is noteworthy that the extensive neutrophil extravasation in the sinus cavity appears to conflict with the small amount of tissue neutrophils in nonallergic chronic sinusitis.…”
Section: Discussionmentioning
confidence: 99%